Assessment of LINAC Source Radiation Dose around Healthy Organs Using Treatment Planning System Calculation - Fardela, Ramacos; Candra, Ega Septryan; Milvita, Dian; Mardiansyah, Dedi; Ridwan, Ridwan; Diyona, Fiqi; Mousa, Almahdi (Journal of Multidisciplinary Applied Natural Science, 2025)
The negative effects of increased radiation dose can impact healthy tissue surrounding the target area, necessitating careful management to minimize side effects and meticulous planning in radiation therapy. This study aims to determine the peripheral dose of a 6 MV photon beam and compare the measured values with the estimates from the Treatment Planning System (TPS). Dose calculations were performed using the Analytical Anisotropic Algorithm (AAA) in the ECLIPSETM TPS on a virtual water phantom with a 6 MV photon beam, delivered by a Clinac CX linear accelerator (LINAC) at Unand Hospital. Photons were used with variations in target depth of 1.5, 5, and 10 cm, as well as variations in measuring distances of 3, 5, 7, 10, and 15 cm outside the irradiation field. The area of irradiation used varied of 5×5 and 10×10 cm2. The measurement results based on the distance of the field edge showed that the dose percentage decreased below 10% when passing a distance of 5 cm for a field area of 5×5 cm2, and for a field area of 10×10 cm2, the dose percentage decreased below 10% after passing a distance of 7 cm from the edge of the irradiation field. The peripheral dose intensity in the area outside the target will decrease along with the increasing measurement distance from the edge of the field and the depth due to the interaction of radiation with the medium, which causes the spread and absorption of photons in the medium.